(untitled) (Psychology Travelogs, 2025)
Emotional intelligence (EI) is a critical factor in effective managerial activity, influencing communication, team motivation, conflict resolution, and decision-making in complex and dynamic environments. This article examines the role of EI in management, focusing on contemporary methods of psychodiagnostics and strategies for its development. Key psychodiagnostic tools, including self-report measures (e.g., EQ-i 2.0, TEIQue), ability-based tests (e.g., MSCEIT), and 360-degree feedback methods (e.g., ECI, Genos EI Assessment), are analyzed for their applicability, strengths, and limitations in assessing EI competencies such as self-awareness, self-regulation, empathy, and social skills. The study highlights practical approaches to EI development, including coaching, training programs, and frameworks like RULER, to enhance managerial effectiveness. Special attention is given to the Ukrainian context, where EI research is emerging, particularly in public sector management. The findings underscore the need for culturally adapted diagnostic tools and structured development programs. Prospects for further research include longitudinal studies, neuroscientific approaches, and the integration of EI training in digitalized work environments. This article provides a comprehensive framework for understanding and fostering EI to improve leadership performance.